Bioprospecting Test of Piper betle Leaf Essential Oil Against Staphylococcus Aureus and Escherichia Coli-Antibiotic Resistant - Anindita, Reza; Beandrade, Maya Uzia; Putri, Intan Kurnia (Program Studi Pendidikan Biologi, FKIP Unpas,, 2024)
One of the efforts to overcome antibiotic resistance is the bioprospection of natural materials that have the potential to be antibacterial. One of the results of distilling natural materials with antibacterial potential is betel leaf essential oil (Piper betle). This study aimed to determine the effect of essential oils on Staphylococcus aureus and Escherichia coli-resistant antibiotics. The design of this study is experimental, with independent variables in the form of essential oils with concentrations of 5%, 10%, 15%, 20%, 25%, and 100%. In contrast, the dependent variable is the diameter of the growth inhibition zone of S. aureus and E.coli bacteria. Essential oil extraction using steam distillation and chemical characterization by GC-MS test. Antibacterial testing uses the Kirb-Bauer method. GC-MS test results were dominant eugenol (3.50%), caryophyllene (3.79%), and Germacrene D (1.19%). The application of essential oils was able to inhibit the growth of S. aureus with inhibition zone diameters of 10.5 mm (moderate), 10.6 mm (moderate), 10.8 mm (moderate), 12.3 mm (strong), 14 mm (strong), and 30.2 mm (very strong), while E. coli was 5.7 mm (moderate), 7.5 mm (moderate), 10.5 mm (moderate), 12 mm (strong), and 30.03 mm (very strong). The results of the ANOVA one-way test showed a value of 11762.7, while the F table was 3.48 (Fcal > Table). This study concludes that administering essential oils with concentrations of 5%, 10%, 15%, 20%, 25%, and 100% can significantly inhibit the growth of S. aureus and E.coli bacteria.